Czas wolny dzieci niepełnosprawnych intelektualnie w opinii rodziców - Kaiser, Izabella (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The study aimed at diagnosing the opinions of parents of children with mild and moderate intellectual disability on the forms and significance of leisure time behaviour. The study revealed that parents, siblings, or other family members were most often partners of leisure for intellectually disabled children. All the respondents declare that they know what their children are doing in their leisure time and who they spend it with. Leisure time appears to be the area of limitless rehabilitation opportunities, and therefore it should occupy a significant position both in scientific research and (perhaps predominantly) in practical activities undertaken to help children with intellectual disability. Extensive activity of the school, family environment and special education teachers themselves is required to implement leisure time as a vital element in the process of revalidation of intellectually disabled children.